The Effect of Regional Transfers on Poverty Reduction in Aceh Province From 2011 to 2024: A Generalized Method of Moments (GMM) Approach - Anggara Pratama Putra (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study analyzes the impact of government spending—including social assistance, financial assistance, grants, and subsidies—on poverty reduction in Aceh Province using the Generalized Method of Moments (GMM) approach. Although the government budget continues to increase, poverty reduction in Aceh remains suboptimal, mainly due to structural and socio-economic challenges exacerbated by the COVID-19 pandemic. One aspect that has been rarely studied is the impact of financial assistance spending, especially in Aceh, which has unique socio-economic characteristics. This study integrates key socio-economic indicators, such as the Human Development Index (HDI) and the Open Unemployment Rate, to analyze their combined impact on poverty levels. The findings show that social assistance and financial assistance have a significant impact but tend to increase poverty. This is due to the dependency that arises from uneven distribution and the lack of sustainable economic empowerment. On the other hand, grants were found to contribute positively to poverty reduction, while subsidies did not show a significant impact. In addition, higher HDI scores were associated with lower poverty rates, while higher unemployment rates were associated with higher poverty rates. These findings highlight the importance of targeted fiscal policies and efficient resource allocation to address the root causes of poverty. This study provides valuable insights for improving policy formulation and implementation of poverty alleviation programs in Aceh, emphasizing the need for a holistic approach that combines human capital development and the creation of sustainable economic opportunities.